Development of polypropylene nanocomposite using nanoclay and multiwall carbon nanotube - Olalekan, Salawudeen Taofeeq (Kulliyyah of Engineering, IIUM, 2011)
Polypropylene is a very important plastic among polyolefins with high performance properties at a moderate cost. Reinforcement of polypropylene (PP) with fibres gives a composite which compared favorably with most engineering polymers. However, research on polymer composites using micro-fillers has reached the limit of optimization because most often the achieved property usually involved a lot of tradeoffs due to high percentage of fillers required. This research was therefore aimed at developing a PP ternary nanocomposite using primarily a modified clay and multiwall carbon nanotube as secondary filler. Production of ternary nanocomposite of polypropylene (PP-Clay/MWCNT) has been achieved by melt intercalation of PP, Clay and MWCNT at predetermined percentages of modified clay, maleic anhydride grafted polypropylene and varying percentage of MWCNT. Operating parameters such as melting temperature, mixing speed and MWCNT content were optimized and statistically analyzed in order to determine the optimum conditions that will favor the production of the composite by using central composite design of surface response. The final composites were characterized for their tensile properties, thermal and chemical resistance properties. Morphological characterization was also conducted to evaluate the properties of the final composite relative to filler dispersion. The results showed that the main parameters which influence the properties of the composite are the melting temperature and percentage MWCNT once the mixing speed is fixed at a moderate value above 100rpm. The statistical analysis using ANOVA indicated that the third order polynomial model fitted for both the tensile strength and Young's modulus are highly significant with p-values of 0.008 and 0.002 respectively while that of elongation at break (E) did not fit into any model considered. The p-value for E using the third order model gave 0.2598 and hence considered insignificant. The regression analysis for tensile strength and Young's modulus gave R2 (actual and adjusted) almost unity. However, there is a wide gap between actual and adjusted R2 for E and hence the reason for high p-value and discrepancy. Finally, the optimum conditions for the production of PP ternary nanocomposite was given to be MWCNT percentage of 0.17wt%, melting temperature of 165oC and 120rpm mixing speed. These conditions yielded a percentage enhancement of 26.20 and 42% in tensile strength and Young's modulus respectively when compared with PP/Clay intermediate binary composite and 57 & 63% respectively when compared with virgin PP used in the study. The result has been justified in the morphological characterization conducted by using XRD, TEM and SEM. The three selected samples with 0.17, 0.45 and 0.61wt% MWCNT performed excellently well with best performance observed in the sample with 0.61wt% MWCNT in terms of chemical and thermal resistances. The samples are therefore recommended for use in the fabrications of biochemical, chemical, and environmental process equipment due to their high stability in acid, alkaline water and bacterial solutions combined with high thermal stability.